The role of Mesothelin signaling in Portal Fibroblasts in the pathogenesis of cholestatic liver fibrosis - Fuji, Hiroaki; Miller, Grant; Nishio, Takahiro; Koyama, Yukinori; Lam, Kevin; Zhang, Vivian; Loomba, Rohit; Brenner, David; Kisseleva, Tatiana (Frontiers in Molecular Biosciences, 2021)
Liver fibrosis develops in response to chronic toxic or cholestatic injury, and is characterized by apoptosis of damaged hepatocytes, development of inflammatory responses, and activation of Collagen Type I producing myofibroblasts that make liver fibrotic. Two major cell types, Hepatic Stellate Cells (HSCs) and Portal Fibroblasts are the major source of hepatic myofibroblasts. Hepatotoxic liver injury activates Hepatic Stellate Cells (aHSCs) to become myofibroblasts, while cholestatic liver injury activates both aHSCs and Portal Fibroblasts (aPFs). aPFs comprise the major population of myofibroblasts at the onset of cholestatic induced injury, while aHSCs are increasingly activated with fibrosis progression. Here we summarize our current understanding of the role of Portal Fibroblasts in the pathogenesis of cholestatic fibrosis, their unique features, and outline the potential mechanism of targeting Portal Fibroblasts in fibrotic liver.